2014
DOI: 10.1097/mib.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Interferon Regulatory Factor 1 and Osteopontin on the Apoptosis of Epithelial Cells Induced by TNF-α in Inflammatory Bowel Disease

Abstract: Our data suggest that during intestinal inflammation, the TNF-α-mediated activation of IRF1 is related to the subsequent suppression of OPN expression, further reducing p-AKT, p-P38, and p-ERK activities and resulting in aggravation of the injury to intestinal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Accumulating evidence has shown that decreased levels of TNF-α in the intestinal tissue and serum reduce IECs apoptosis in UC. [39] In line with this, in this study, we found that treatment with HNG significantly decreased caspase-3 activities compared to that in TNBS-treated rats. Therefore, we speculated that HNG prevented apoptosis caused by TNF-α in intestinal epithelial cells in UC.…”
Section: Discussionsupporting
confidence: 82%
“…Accumulating evidence has shown that decreased levels of TNF-α in the intestinal tissue and serum reduce IECs apoptosis in UC. [39] In line with this, in this study, we found that treatment with HNG significantly decreased caspase-3 activities compared to that in TNBS-treated rats. Therefore, we speculated that HNG prevented apoptosis caused by TNF-α in intestinal epithelial cells in UC.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, elevated plasma levels were shown to be correlated with disease activity (Komine-Aizawa et al 2015). However, reduced expression of OPN in UC and CD as compared with normal controls was found in a cohort of Chinese patients (Tang et al 2014), although this difference may be explained by a focus on expression in epithelial rather than inflammatory cells. Interestingly, a haplotype consisting of 8 single-nucleotide polymorphisms in the OPN gene was found to exhibit significant associations with CD susceptibility (Glas et al 2011), further supporting an association of OPN with this disease.…”
Section: Opn In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…In addition to IBD, other inflammatory processes may condition intestinal homeostasis, such as food allergies. Compelling evidence during the past decade have demonstrated that T cell-mediated mechanisms promote mucosal inflammation in IBD (Neurath et al, 2001;Sturm et al, 2008;Gerner et al, 2013) and dramatically compromise the epithelial cell compartment (Siggers & Hackam, 2011;Planell et al, 2012;Tang et al, 2014;Thagia et al, 2014).…”
mentioning
confidence: 99%